Sensory Transduction in Peripheral Nerve Axons Elicits Ectopic Action Potentials - Hoffmann, Tal (J Neurosci, 2008)
Sensory properties of unmyelinated axons in the isolated rat sciatic nerve have been revealed previously by measuring stimulated neuropeptide release in response to noxious stimuli. In addition, axonal sensitization by inflammatory mediators has been demonstrated and shown to depend on the heat- and proton-activated ion channel transient receptor potential vanilloid receptor-1. It was unclear whether this responsiveness is accompanied by ectopic generation of action potentials, which may play a crucial role in painful neuropathies. We explored this hypothesis using the isolated mouse skin-nerve preparation. This method enabled us to directly compare the sensory properties of axons in the peripheral nerve with their characterized cutaneous terminals in the receptive field using propagated action potentials as an index of axonal activation. Single-fiber recordings from 51 mechanosensitive mouse C-fibers revealed that a majority of the polymodal nociceptors responded with an encoding discharge rate to graded heating of the cutaneous receptive field (n = 38) as well as of the saphenous nerve carrying the fiber under investigation (n = 25; 66%). Axonal heat responses paralleled those of the receptive fields with regard to thresholds and discharge rates (41.5 ± 4.3°C; 7.7 ± 9.6 spikes in a 20 s 32–48°C ranged stimulation). In contrast, axonal mechanosensitivity was poor and noxious cold sensitivity more rarely encountered. In conclusion, peripheral nerve axons exhibit sensory transduction capacities similar to their nociceptive terminals in the skin with respect to noxious heat, although not to mechanical and cold sensitivity. This may become a source of ectopic discharge and pain if axonal heat threshold drops to body temperature, as may be the case during inflammation-like processes in peripheral nerves.